2008
DOI: 10.1159/000166600
|View full text |Cite
|
Sign up to set email alerts
|

Male Sex Hormones May Influence the Symptoms of Irritable Bowel Syndrome in Young Men

Abstract: Aims: To evaluate the sex hormone status of young male patients with irritable bowel syndrome (IBS) and to investigate whether there were any differences in bowel symptoms related to the hormone levels. Methods: Thirty-eight young male patients with IBS were compared with 20 healthy young men. Details of symptoms were collected by a structured questionnaire. Each subject underwent a blood test and colonoscopy. The blood test included serum testosterone, free testosterone, sex hormone-binding globulin (SHBG), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…48 A recent study showed that middle-aged men with IBS tended to have lower levels of luteinizing hormone than healthy men, and that IBS symptomatology tended to be inversely related to testosterone. 49 In addition, Kim et al 50 demonstrated elevated levels of sex hormone-binding globulin (SHBG) as well as testosterone, in young, male IBS patients compared to controls, suggesting that high SHBG concentration may play a role in the development of IBS.…”
Section: Hormonal Factorsmentioning
confidence: 99%
“…48 A recent study showed that middle-aged men with IBS tended to have lower levels of luteinizing hormone than healthy men, and that IBS symptomatology tended to be inversely related to testosterone. 49 In addition, Kim et al 50 demonstrated elevated levels of sex hormone-binding globulin (SHBG) as well as testosterone, in young, male IBS patients compared to controls, suggesting that high SHBG concentration may play a role in the development of IBS.…”
Section: Hormonal Factorsmentioning
confidence: 99%
“…In fact, testosterone levels correlated negatively with pain thresholds of rectal distension and overall well‐being in IBS patients . Others have reported that elevated levels sex hormone‐binding globulin level may influence the symptoms of IBS in young men . Interestingly, a highly significant reduction in male‐trait scores in men with IBS has been published …”
Section: The Role Of Sex and Stress In Ibsmentioning
confidence: 99%
“…230 Others have reported that elevated levels sex hormone-binding globulin level may influence the symptoms of IBS in young men. 231 Interestingly, a highly significant reduction in male-trait scores in men with IBS has been published. 232 Clinical manifestations of IBS are associated at gut level with mucosal inflammation, visceral hypersensitivity, and intestinal permeability.…”
Section: The Role Of Sex and Stress In Ibsmentioning
confidence: 99%
“…IBS is a common and debilitating functional GI disorder of unclear etiology that is characterized by abdominal pain and altered stool patterns (diarrhea, constipation, or both). Two studies in which testosterone levels were measured by immunoassay in small groups of males with IBS found associations between testosterone levels and GI symptoms 25,26 , suggesting that altered androgen signaling might play a role in IBS. To test this possibility more rigorously, we used a highly-sensitive mass spectrometry assay to measure serum total testosterone, percent free testosterone, and DHT levels in 208 patients with IBS at the baseline visit of a randomized controlled trial designed to test a therapeutic intervention (Clinical Trials.gov NCT02802241) 27 .…”
Section: Wnt1mentioning
confidence: 99%